Modulating wheelchair navigation in patients with spatial neglect. - Punt, T; Kitadono, K; Hulleman, J; Humphreys, G; Riddoch, M (2011)
Patients who have had a stroke resulting in the deficit of visuo-spatial neglect are normally not provided with a powered wheelchair, as they are either considered or found to be unsafe navigating about their environment. As these patients are relatively unlikely to regain functional mobility by walking, the denial of alternative forms of mobility is of particular concern. Modest progress has been made over the past two decades with regards to the rehabilitation of neglect but there have been calls for further research which addresses "real world" measures of independence such as wheelchair navigation. In this study, we investigated the ability of patients with neglect to improve their performance when navigating a powered wheelchair by using theoretically-driven strategies that have shown promise in previous studies (spatial cueing and limb activation). Strategies were applied and tested in the most realistic and practical manner for each individual, based on their abilities and concurrent deficits. Performance was improved by the experimental strategies. The data suggest it is possible to apply theoretically-driven strategies to improve wheelchair navigation in patients with neglect and are supportive of further studies that could lead to improved access to powered mobility by this population in the future.